2017
DOI: 10.3329/bjp.v12i2.32010
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and biological activity of Nepeta cilicica

Abstract: <p>In the present study, aerial parts of <em>Nepeta cilicica</em> were hydro-distilled for the essential oil. Furthermore, air-dried plant materials were extracted with methanol. According to GC-MS results, 35 compounds were characterized in the oil (totally 92%). Caryophyllene oxide, β-caryophyllene and spathulenol (28.2, 8.9 and 4.2%) were found as main components of the oil. Sixteen compounds were detected by LC/MS, most of which were caffeoylquinic acid, luteolin and apigenin derivatives,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In addition, the concentration of the different components in the methanol and water extracts might be different, and this was not specified in our data. In accordance with our results, the presence of flavones and hydroxycinnamic acid in the members of the Nepeta genus was reported in earlier studies [23][24][25][26][27].…”
Section: Resultssupporting
confidence: 94%
“…In addition, the concentration of the different components in the methanol and water extracts might be different, and this was not specified in our data. In accordance with our results, the presence of flavones and hydroxycinnamic acid in the members of the Nepeta genus was reported in earlier studies [23][24][25][26][27].…”
Section: Resultssupporting
confidence: 94%
“…e DCM: methanol extract and compound B1 from T. welwitschii inhibited the production of eDNA and may be one of the mechanisms of disrupting biofilm formation by P. aeruginosa. us, phytochemicals from T. welwitschii may serve as antibiofilm and Anti-inflammatory and antihyperglycemic activities [40,41] Malonyl-monocinnamoylquinic acid Antibacterial and antifungal activities [42]…”
Section: Discussionmentioning
confidence: 99%
“…But the methanol extract showed lower inhibitory effect. İşcan et al [18] demonstrated that methanol extract of N. cilicica exhibited potent inhibition against S. aureus and C. tropicalis (47 µg/mL MIC). The ethanolic extract of N. trachonitica has demonstrated a strong antibacterial effect against E. coli (inhibition zone: 12.0 ± 1.24).…”
mentioning
confidence: 99%